2023
DOI: 10.3389/fevo.2023.1146850
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based grassland aboveground biomass estimation and its response to climate variation in Southwest China

Abstract: The demand for accurate estimation of aboveground biomass (AGB) at high spatial resolution is increasing in grassland-related research and management, especially for those regions with complex topography and fragmented landscapes, where grass and shrub are interspersed. In this study, based on 519 field AGB observations, integrating Synthetic Aperture Radar (SAR; Sentinel-1) and high-resolution (Sentinel-2) remote sensing images, environmental and topographical data, we estimated the AGB of mountain grassland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Additionally, the RMSE and the MAE measured the deviation between actual and simulated grassland AGB values. Smaller values for the RMSE and MAE signified a smaller difference between the actual and simulated values, thereby indicating higher accuracy in the constructed inversion model (Zhang et al, 2023).…”
Section: Type Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the RMSE and the MAE measured the deviation between actual and simulated grassland AGB values. Smaller values for the RMSE and MAE signified a smaller difference between the actual and simulated values, thereby indicating higher accuracy in the constructed inversion model (Zhang et al, 2023).…”
Section: Type Equationmentioning
confidence: 99%
“…Moreover, there is an asynchronous relation between grassland biomass and changes in precipitation. Zhang et al (2023) researched moisture conditions affecting both the aboveground and belowground biomasses of grasslands during different stages of vegetation flowering and fruiting. Wang Q. et al (2022) found that increased temperatures have a significant effect on the biomass and species diversity of degraded grasslands in their natural recovery state, although they have little effect on natural grasslands.…”
Section: Impacts Of Climate Change On Grassland Aboveground Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have obvious spatial and temporal limitations, affecting their versatility and portability [28]. Therefore, these empirical methods are difficult to apply to large-scale, long time-series, and specific growth period studies [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Quan et al [20] used the PROSAIL model and Landsat-8 spectral data to invert the LAI and Cm to estimate the AGB. He et al [30] estimated the grassland AGB in the Zoigê Plateau using the lookup table (LUT) method based on the PROSAIL model and MODIS products. However, due to the complexity of RTM, a large amount of computation is required to estimate grassland AGB, resulting in low efficiency.…”
Section: Introductionmentioning
confidence: 99%